Batson: Wrong Name for National Steel Orchestra - Nero, Sean (Trinidad Guardian)
Dr. Dawn Batson wants all to know that the correct name for the National Steel Orchestra is "The Trinidad and Tobago National Steel Orchestra". Batson, who is chairman of the orchestra, was clearing the air on the terminology.
Keywords: Steel bands (Music) -- Trinidad and Tobago; Steel bands (Music) -- Administration -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Trinidad and Tobago National Steel Orchestra; National Steel Orchestra of Trinidad and Tobago (NSOTT)